2016
DOI: 10.1111/ajt.13725
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Costimulatory Blockade to Generate Regulatory T Cells From Patients Awaiting Kidney Transplantation

Abstract: These authors contributed equally to this work.Short-term outcomes of kidney transplantation have improved dramatically, but chronic rejection and regimen-related toxicity continue to compromise overall patient outcomes. Development of regulatory T cells (Tregs) as a means to decrease alloresponsiveness and limit the need for pharmacologic immunosuppression is an active area of preclinical and clinical investigation. Nevertheless, the immunomodulatory effects of end-stage renal disease on the efficacy of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…Here, we have expanded polyclonal Tregs and tested their safety after reinfusion in kidney transplant recipients on tacrolimus, mycophenolate mofetil and corticosteroids. While Tregs have been previously isolated from uremic patients , this is the first report showing that isolation and expansion of Tregs is not only possible from kidney transplant recipients on immunosuppression but also feasible in sufficient numbers for in vivo therapy. The Treg infusions were well tolerated without cytokine release, infusion reactions, or infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have expanded polyclonal Tregs and tested their safety after reinfusion in kidney transplant recipients on tacrolimus, mycophenolate mofetil and corticosteroids. While Tregs have been previously isolated from uremic patients , this is the first report showing that isolation and expansion of Tregs is not only possible from kidney transplant recipients on immunosuppression but also feasible in sufficient numbers for in vivo therapy. The Treg infusions were well tolerated without cytokine release, infusion reactions, or infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that regulatory T cells may be partially spared of the suppressive effects of PI3K inhibitors compared with CD4 + lymphocytes. Therefore, PI3K and MEK inhibitors might be useful primarily, or as adjunct to costimulatory blockade in ex vivo Treg manufacturing to enhance Treg yields from a mixed starting population. Moreover, they may preferentially target Teff responses in vivo , while relatively preserving Treg activation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study reported the generation of Tregs from the PBMCs of uremic recipients and of healthy donors using ex vivo co-stimulation with belatacept (a second-generation CTLA4Ig) during a mixed lymphocyte reaction21. It appears to be clinically feasible to use Treg to decrease alloresponsiveness and to limit the need for pharmacologic immunosuppressants during kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%